Grammatical Differences in British and American English in the Students’ Instagram Accounts - Christanty Yudha Bestari, Ade; Haris Mayekti, Meilina; Faiza, Dinar (Educalitra: English Education, Linguistics, and Literature Journal, 2022)
This research contains an analysis of grammatical differences in British and American English in the students’ Instagram accounts of the Nahdlatul Ulama University of Purwokerto (UNU Purwokerto). The purpose of this study was grammatical differences in British and American English that were used by students in developing writing skills. This study uses a qualitative approach using descriptive analysis methods. The sampling technique was carried out by means of purposive sampling of the captions used for English writing practice. The Instagram accounts were analyzed 50 students accounts. The results of this study are; (1) Grammatical Differences in British and American English, (2) The Using of Grammatical British English and American English on Caption Writing.